Extraction of a bullet floating in the pulmonary artery after a gunshot wound - Caushi, Fatmir (J Int Med Res, 2021)
BACKGROUND: Patients with thoracic trauma caused by gunshots face a high risk of death, and medical staff often encounter technical difficulties in resolving these cases. Most gunshot wounds result in an entrance and exit wound. In cases with no exit wound, missiles are seen in other areas with screening radiographs. The bullet may migrate depending on gravity, coughing, swallowing, blood flow, or local erosion. CASE PRESENTATION: We present the case of a teenager who was hospitalized in critical condition owing to a left hemithorax injury caused by an improvised explosive device. The patient underwent two surgeries: an anterior left thoracotomy during which a hole in the myocardium was sutured, and after radiography, anterolateral right thoracotomy was performed, in which a deformed projectile was found at the level of the intermediate right pulmonary artery. CONCLUSIONS: This case highlights the crucial importance of repeated imaging to assess the possibility of projectile migration within the cardiovascular system in similar cases of penetrating injury. Immediate surgery was necessary and very important for the survival of our patient, despite the difficulties presented by this complicated case.